2014
DOI: 10.1021/jp502470j
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Atomic Hydrogen with Formic Acid and Carbon Monoxide in Solid Parahydrogen I: Anomalous Effect of Temperature

Abstract: Low-temperature condensed phase reactions of atomic hydrogen with closed-shell molecules have been studied in rare gas matrices as a way to generate unstable chemical intermediates and to study tunneling-driven chemistry. Although parahydrogen (pH2) matrix isolation spectroscopy allows these reactions to be studied equally well, little is known about the analogous reactions conducted in a pH2 matrix host. In this study, we present Fourier transform infrared (FTIR) spectroscopic studies of the 193 nm photoinduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 58 publications
4
23
0
Order By: Relevance
“…50,78,79 In particular, the formation of carboxyl radical by local reaction of hot OH radicals with CO molecules was observed in argon matrices by Mielke et al 79 Very recently, Paulson et al reported spectroscopic characterization of this radical resulting from reaction of hydrogen atoms with formic acid in a solid para-hydrogen matrix. 80 On the other hand, such a reaction was not found in a solid krypton matrix. 81 Meanwhile, here we present the first observation of formation of the HOCO radical as a result of radiation-induced evolution of the CO 2 −H 2 O system in condensed media.…”
Section: Resultsmentioning
confidence: 99%
“…50,78,79 In particular, the formation of carboxyl radical by local reaction of hot OH radicals with CO molecules was observed in argon matrices by Mielke et al 79 Very recently, Paulson et al reported spectroscopic characterization of this radical resulting from reaction of hydrogen atoms with formic acid in a solid para-hydrogen matrix. 80 On the other hand, such a reaction was not found in a solid krypton matrix. 81 Meanwhile, here we present the first observation of formation of the HOCO radical as a result of radiation-induced evolution of the CO 2 −H 2 O system in condensed media.…”
Section: Resultsmentioning
confidence: 99%
“…Similar H atom tunneling reactions have been observed for the reactions of H atoms with HONO (∼21 kJ mol –1 ), CH 3 OH (∼35 kJ mol –1 ), , H 2 NC­(O)H (∼26 kJ mol –1 ), C 5 H 5 N (∼8 kJ mol –1 ), HC­(O)­OCH 3 (∼41 and 46 kJ mol –1 for the formation of HC­(O)­CH 2 and C­(O)­OCH 3 radicals, respectively), and CH 3 CONH 2 (∼41 kJ mol –1 ); predicted barriers are provided in parentheses. Paulson et al photolyzed HC­(O)­OH in solid p -H 2 at 1.7 K with laser light at 193 nm and observed tunneling reaction H + HC­(O)­OH because some H atoms were produced from photolysis; the reaction proceeded even after photolysis was terminated, resulting in the formation of HOCO from abstraction of the hydrogen on the carbon atom rather than the hydroxyl hydrogen. Similarly, in this work the H + CH 3 C­(O)­OH reaction proceeds through H-abstraction of the alkyl (CH 3 ) group that leads to the formation of the •CH 2 C­(O)­OH radical.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we decided to reinvestigate this system at two different temperatures, 1.8 and 4.3 K, respectively, to measure the effect of temperature on the reaction rate. Another reason to revisit this system is the anomalous results we have recently measured for other H atom reactions in solid pH 2 . For example, in the case of the H + N 2 O → cis -HNNO reaction we observed a very strange temperature dependence .…”
Section: Introductionmentioning
confidence: 99%